Temporal stability and discriminant validity of the Beck Anxiety Inventory - Pagano, Alejandro Emilio (2021)
Background: Anxiety disorders are the most prevalent worldwide, followed by depressive disorders. The Beck Anxiety Inventory (BAI; Beck et al., 1988) has been developed to assess the severity of anxiety symptoms and perform a differential diagnosis between anxiety and depression disorders. Objective: To examine the temporal stability of the BAI in its version adapted to Argentina and obtain evidence of discriminant validity. Method: In a sample of 52 people, the intraclass correlation coefficient was analyzed. Then, in a sample of 225 people, a correlation analysis between BAI scores and the Beck Depression Inventory-II (BDI-II; Beck et al., 2006) was performed; subsequently, an exploratory factor analysis (EFA) with reagents from both instruments was conducted and the heterotrait-monotrait ratio of correlations (HTMT) was calculated. Results: The intraclass correlation coefficient was .82 (95% CI = .69 - .90). The correlation between the BAI and the BDI was .56 (moderate effect size). The EFA showed two well-differentiated factors and an HTMT proportion value of .66 (95% CI = .55 - .74) was found. Conclusions: An adequate temporal stability is observed and evidence of the discriminant validity of the instrument is provided.   Authorship contributionAEP: conception and design of the study, interpretation of the data and final revision of the manuscript.NAV: conception and design of the study, interpretation of the data and final revision of the manuscript.